1999
DOI: 10.1046/j.1365-2168.1999.0707a.x
|View full text |Cite
|
Sign up to set email alerts
|

Two-year follow-up after acute thromboembolic lower limb ischaemia: the importance of continuing warfarin treatment

Abstract: BACKGROUND: The Vascular Surgical Society carried out an audit of follow-up after acute thromboembolic lower limb ischaemia. METHODS: The audit of acute lower limb ischaemia was done between 1 January and 31 March 1996 and included 474 patients. This report describes a 2-year follow-up of patients with a diagnosis of thrombosis or embolism who survived 30 days. Details were obtained for 214 (75 per cent) of 287 patients: half (107) were men, and the age range was 21-96 (mean 74) years. RESULTS: Amputation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…1,8 It has been suggested that this change is the result of improved prescribing of anticoagulants for patients in atrial fibrillation and a decrease in incidence of rheumatic heart disease. 5,9,26,27 The present review demonstrates that around 10 patients who present to a single vascular unit each year still require surgical embolectomy. The majority are primary referrals from a local catchment population of about 500,000 with the remainder being tertiary referrals from southeast London and Kent (up to 4 million people).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…1,8 It has been suggested that this change is the result of improved prescribing of anticoagulants for patients in atrial fibrillation and a decrease in incidence of rheumatic heart disease. 5,9,26,27 The present review demonstrates that around 10 patients who present to a single vascular unit each year still require surgical embolectomy. The majority are primary referrals from a local catchment population of about 500,000 with the remainder being tertiary referrals from southeast London and Kent (up to 4 million people).…”
Section: Discussionmentioning
confidence: 81%
“…3,4 Patients presenting with acute embolic occlusions tend to be elderly with coexisting medical problems. These factors have contributed to a persistent risk of amputation and death after surgical embolectomy [4][5][6][7][8][9][10][11] (Table I). Our experience did not reflect these findings, so we carried out this review to determine the prevalence and outcome of all surgical embolectomies presenting to our unit over a 3-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Acute limb ischaemia (ALI) is a significant cause of morbidity and mortality in our increasingly elderly population, with hospital mortality rates ranging from 17 to 30% [1][2][3] and amputation rates of 5-16% in survivors [4,5]. The cause of ALI is peripheral embolism in approximately 40% of cases, with the heart being the commonest embolic source [6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, lower limb revascularization is a common procedure, with large numbers of published series of outcome following acute and chronic ischemia. [23][24][25][26][27][28] The purpose of this study was to review a single center's experience of acute and chronic upper limb revascularization over a 20-year period. The outcome of surgical and endovascular intervention is presented and compared with published series of upper and lower limb revascularization.…”
mentioning
confidence: 99%